Darlehen und Schuldscheine im Frankenreich (6. bis 9. Jahrhundert) - Lößlein, Horst; Walther, Christoph (Das Mittelalter, 2022)
Loans and credit relations are only very rarely subject of narrative sources from the early Middle Ages. Only Gregory of Tours mentions individuals taking out loans in the regnum Francorum. According to him, these loans were secured by the issuance of cautiones, promissory notes, which the creditor kept for safekeeping until the debt was repaid. Unfortunately, cautiones were only of interest until the loan was repaid and thus were not archived but destroyed. However, ten of these promissory notes have survived as formulae (anonymized documents that served as models of how to compose corresponding charters or letters) in West Frankish collections. These can be used to draw a colourful picture of early medieval credit relations. While the loans are always quantified in monetary terms, the pledges of collateral reveal a wide range of possibilities, ranging from personal services to the temporary transfer of land. The latter are closely intertwined with the payment of interest, for example, when the creditor is allowed to keep the crops of the land. At the same time, collateral pledges, such as the obligation to perform regular services, can also be used to draw conclusions on the social backgrounds of the debtors as well as the creditors, revealing the importance of the neighborhood for local credit relations. Keywords Loan; Promissory Note; Early Middle Ages; Credit Relations; Collateral